Interorganizational trust and agency costs in credit relationships between savings banks and SMEs - Hirsch, Bernhard; Nitzl, Christian; Schoen, Matthias (Journal of Banking & Finance, 2018)
We analyze the impact of trust on agency costs in relationships between savings banks and SMEs as well as the mediating effects of hard information on interorganizational trust between these two actors. We tested six hypotheses using a structural equation model based on partial least squares. Study data were obtained from two German savings banks and dyadic questionnaires of relationship managers and credit risk officers. Our results provide evidence that interorganizational trust reduces agency costs by directly and indirectly increasing the quality of credit negotiations by lowering the bank's monitoring intensity via habitualization. Surprisingly, institutionalized trust increases the banks’ monitoring intensity.